Impact Of Distribution Generation On An Overcurrent Protection In Power System Network - Che Ros, Nur Aida Hazirah (2020)
In power system network, protection system is an important element that needs to be concerned because it is able to detect the presence of interference and can prevent damage from occurs. The protective device is needed to isolate the fault element quickly as possible to keep the healthy section of the system in normal operation when the faults occur in the power system network. The protection system can improve the reliability of the system to maintain the continuity of supply to the load. Overcurrent protection is among the important protection scheme on the power system network. The basic element of the overcurrent protection is overcurrent relay. An overcurrent relay will operate when the current exceeds its pick up value, but some problems have been raised due to the overcurrent relay fails to operate in the presence of a fault. The aim of overcoming the problems is by taking into the consideration of relay operation time of overcurrent protection for the power system network. The relay operation time will be analyzed. PSCAD software has been used as simulating tools to validate the model and analysis of the overcurrent protection system. The overcurrent protection analysis indicates the protection, performance based on the type of relay characteristic curve (standard inverse, very inverse and extremely inverse), type of fault applied (single line to ground, double line to ground and three phase to ground fault) and location such as source 132kV, grid 33kV, load 33kV and load 2 (11kV). Besides, the characteristic curve standard IEC 60255 and IEE C37.112 are used in order to analyze the effect of relay operation time. The result will be studied in order to understand the performance of the overcurrent protection system in the power system network.